2018
DOI: 10.1080/17843286.2018.1482087
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and willingness to perform CPR: a survey amongst Flemish schoolchildren, teachers and principals

Abstract: Objectives Training children in cardiopulmonary resuscitation (CPR) is one of the strategies to increase bystander CPR in society. Reinforcing knowledge and awareness and increasing willingness to perform bystander CPR contributes to a better outcome after cardiac arrest. We questioned schoolchildren, teachers and principals about their awareness of the importance of CPR and about their willingness to perform CPR. Methods During a four-month period, Flemish schoolchildren aged 10-18 years, teachers and princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…29 Less than half of the respondents were willing to provide simple assistance, such as checking consciousness and breathing and dialling 120. Only 34.1% of the respondents were willing to perform CPR on strangers, which was lower than Belgium (68.0%) 25 and Germany (72.3%), 30 but was similar to Tianjin (44.4%). 14 This finding may be related to the social environment and culture of China.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…29 Less than half of the respondents were willing to provide simple assistance, such as checking consciousness and breathing and dialling 120. Only 34.1% of the respondents were willing to perform CPR on strangers, which was lower than Belgium (68.0%) 25 and Germany (72.3%), 30 but was similar to Tianjin (44.4%). 14 This finding may be related to the social environment and culture of China.…”
Section: Discussionmentioning
confidence: 83%
“…The results showed that only 33.6% of the respondents had taken part in CPR training, much lower than Norway (89%). 23 Only 45.5% of the college students were willing to attend CPR training, far lower than New Zealand (63%), 24 Belgium (77.0%) 25 and Wuhan, a city in Central China (88.3%). 26 These findings may be related to respondents' lack of CPR knowledge and awareness of the importance of training and performing bystander CPR.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the widespread ignorance regarding the use of AEDs, defibrillation is a critical component of the survival chain. As a result, it is necessary to educate teachers about the use of AED 30 . In Malaysia, AEDs have been installed in various locations, including malls, airports, and even specific sports complexes and schools.…”
Section: Discussionmentioning
confidence: 99%
“…Correct answers were worth one mark, while incorrect answers carry no marks. The attitudes and willingness to teach and perform CPR were measured using a 4-point Likert scale with 6 and 7 items, respectively 30 . The survey's validity and reliability were previously evaluated.…”
Section: Research Instrumentsmentioning
confidence: 99%
“…It seems that there are two main difficulties concerning providing first aid by non-professionals -the lack of appropriate training and anxiety about performing CPR. The studies have shown that despite some improvement, unwillingness to perform CPR is ever-present in the relevant number of questioned people [13][14][15]. Most studies reveal that the only way to address this issue is by providing high-quality CPR training [16][17][18].…”
Section: Discussionmentioning
confidence: 99%